Beyond community characteristics: a leader's gender and local government adoption of energy conservation practices and redistributive programmes. Issue 2 (1st February 2021) - Homsy, George C.; Lambright, Kristina T.
ABSTRACT: Most research examining factors associated with local government adoption of sustainability practices focuses on the impact of community characteristics. Little is known about whether adoption is also related to the characteristics of the leaders in these jurisdictions. To address this gap in the literature, this exploratory study uses data from a national survey of U.S. local governments ( n = 1, 672) to examine the potential correlation between adoption of certain sustainability practices and the gender of a jurisdiction's highest elected official. Our regression models find that jurisdictions led by women were more likely to have adopted redistributive programmes and practices encouraging community-based energy conservation. But, there is no correlation between a local government's adoption of measures promoting government energy conservation and its leader's gender. Future research should explore whether female leaders' greater openness to citizen involvement in the policymaking process and women's socialisation to focus on communal rather than individual interests help account for our findings.